Juízo e analiticidade em Kant - Bergamasco, Alexsandro de Souza (2017)
This dissertation discusses the notion of analyticity in Kant and its reception on the recent Kantian literature. According to Kant, human knowledge is discursive, that is, through concepts. Knowing involves the awareness of characteristics of objects and the classification of such characteristics in such a way that they can be represented conceptually in judgments. Judgments can be, as far as their justification is concerned, a priori or a posteriori. A priori judgments, in turn, can be analytic or synthetic. Kant characterizes analyticity by appeal to four criteria: that of conceptual containment; that of contradictory negation; that of subject- predicate identity; that of conceptual elucidation. There are several controversies around the comprehension and justification of these criteria, in particular as regards the criterion of conceptual containment. Although such controversies go back to the first decade of publication of the Critique of Pure Reason, especially the controversy with Eberhard, they extend to our days, with commentators as Allison, Hanna, Van Cleve and Anderson. The divergences concern the interpretation of the distinction between analytic and synthetic judgments, the number of criteria of distinction presented by Kant, and especially the question of which criterion could be considered the most fundamental.